The Dynamics of Group Formation Among Leeches - Bisson, Giacomo; Bianconi, Ginestra; Torre, Vincent (Frontiers in Physiology, 2012)
Leeches exploring a new environment continuously meet each other and merge in temporary groups. After 2-3 hours, leeches become attracted to each other eventually forming a large and stable group. When their number is reduced, leeches remain solitary, behaving independently. Group formation is facilitated by body injection of serotonin (5-HT) and the level of endogenous 5-HT is elevated in leeches forming a large group. In contrast, intravenous injection of 5-HT antagonists prevented injected leeches from joining a large group of conspecifics. When sensilla near the head were ablated or the supraesophageal ganglion disconnected, leeches remained solitary, but explored the environment swimming and crawling. These results suggest that group formation is initiated by a release of 5-HT triggered by sensilla stimulation and its dynamics can be explained by the establishment of a reinforcement dynamics, as observed during human group formation. As 5-HT affects social interactions also in humans, group formation in leeches and humans share a similar dynamics and hormonal control.